2015
DOI: 10.4102/sajp.v71i1.234
|View full text |Cite
|
Sign up to set email alerts
|

Level of physical activity of health professionals in a district hospital in KwaZulu-Natal, South Africa

Abstract: BackgroundHealth professionals have a role to play in the promotion of physical activity in order to prevent the ever-increasing burden of diseases associated with physical inactivity. Determination of the level of physical activity amongst health professionals managing patients presenting with various lifestyle-related conditions is most pertinent.ObjectThe purpose of the present study was to ascertain the level of physical activity of health professionals at Estcourt Hospital in KwaZulu-Natal Province.Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
20
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 25 publications
5
20
0
1
Order By: Relevance
“…Health professional whose ages less than 40 years were 3.5 times more likely to engage in physical activity compared with who aged ≥ 40 years. This result is in line with a study done in South Africa showed that Younger participants (< 40 years old) were found to be more active than older participants (≥40 years old) [35]. This can be explained by the fact that when age increases fatigability will also increase.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Health professional whose ages less than 40 years were 3.5 times more likely to engage in physical activity compared with who aged ≥ 40 years. This result is in line with a study done in South Africa showed that Younger participants (< 40 years old) were found to be more active than older participants (≥40 years old) [35]. This can be explained by the fact that when age increases fatigability will also increase.…”
Section: Discussionsupporting
confidence: 91%
“…Out of the Africa continent, the level of physical activity ranges from 27.5-82% [11][12][13][14]. In Africa, health care workers' physical activity ranges from 20.8-79.2% [15][16][17]. A study done in Addis Ababa showed that 73.7% of healthcare professionals as having a moderate level of physical activity.…”
Section: Introductionmentioning
confidence: 99%
“…Similar findings were observed in a study done by Kunene and Taukobong,[22] very few engaged in vigorous (23.9%) and moderate (37.6%) sport and moderate, fitness, or recreation physical activities.…”
Section: Discussionsupporting
confidence: 90%
“…On the other hand, Kunene and Taukobong[22] found that nearly two-fifth (38.5%) engaged in vigorous and almost half (49.5%) in moderate work-related physical activities for at least 10 min continuously. It was observed that the mean number of days spent by the participants in the age group of 31–40 years were less when compared to other age groups.…”
Section: Discussionmentioning
confidence: 99%
“…This result is in line with the findings of similar studies done elsewhere, worldwide, where doctors and other healthcare professionals were noted to be relatively inactive at work in a variety of disciplines. [4][5][6][7][9][10][11][12][13][14][15][16] All the studies assessing doctors' physical activity levels while at work revealed that doctors fall into the so-called 'low active' category as classified by Tudor-Locke and Bassett, [8] i.e. daily activity ranging between 5 000 and 7 499 steps.…”
Section: Discussionmentioning
confidence: 99%